Biotransformations versus chemical modifications: new cytotoxic analogs of marine sesquiterpene ilimaquinone. Issue 44 (2nd November 2016) - Boufridi, Asmaa; Petek, Sylvain; Evanno, Laurent; Beniddir, Mehdi A.; Debitus, Cécile; Buisson, Didier; Poupon, Erwan
Graphical abstract: Highlights: An intrinsically cytotoxic natural product was chosen for bioconversion studies. Original transformations were observed with a Mucor sp. strain. Stereoselectivity of epoxidation differs from classic epoxidation reagents. New analogs are also cytotoxic. Abstract: Highly biologically active marine sesquiterpene ilimaquinone was selected for chemical modifications. Its biotransformation was investigated using a combinatorial approach as an original way to screen different strains of microorganisms. Mucor circinelloides ATCC 8541 was able to structurally modify ilimaquinone into three different compounds. A stereospecific epoxidation was observed and compared to chemical epoxidation. A hydroxylation of the decalin ring was also observed as well as an unexpected substitution on the quinone ring by ethanolamine. Compounds were evaluated against several cell lines.